(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In this article, speaking manners are discussed as a part of the cultural minimum. In particular, the choice of speech etiquette rules has an impact on learning a foreign language. The history of language can be traced back to the prehistoric era when speech etiquette first emerged. According to the members of the ancient civilization, human speaking activity can directly affect people, animals, and the environment; controlling this activity is primarily related to the desire to produce certain events or, on the other hand, to avoid them.